2021
DOI: 10.3168/jds.2020-19761
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolome alteration in dairy cows with left displaced abomasum before and after surgical correction

Abstract: Left displaced abomasum (LDA) leads to substantial changes in the metabolism of dairy cows. Surgical correction of LDA can rapidly improve the health of cows; however, changes in metabolism following surgery are rarely described. To investigate the changes of plasma metabolome in cows with LDA before and after surgical correction, blood samples were collected from 10 healthy postpartum cows and 10 cows with LDA on the day of diagnosis, then again from the LDA cows 14 d after surgery. Serum nonesterified fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…3A ). In our previous study, we identified 102 metabolites in the plasma which differed between LDA and healthy dairy cows ( 8 ). Therefore, we integrated the plasma metabolome with the fecal metabolome ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3A ). In our previous study, we identified 102 metabolites in the plasma which differed between LDA and healthy dairy cows ( 8 ). Therefore, we integrated the plasma metabolome with the fecal metabolome ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… a LDA, left displaced abomasum; NEFA, non-esterified fatty acid; BHBA, β-hydroxybutyric acid; RQUICKI, revised quantitative insulin sensitivity check index; TG, triglyceride; ALT, alanine aminotransferase; CHOL, cholesterol; TP, total protein; ALB, albumin; GLOB, globulin; total bilirubin, TBIL. b Production data were obtained from our previous report ( 8 ), including parity, days in milk, and milk yield. c P < 0.01 compared to healthy cows using two-tailed Student’s t test.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma samples were analyzed using an ultra-high-performance liquid chromatography system (1290 Infinity II, Agilent Technologies, Santa Clara, CA, USA) coupled with time-of-flight mass spectrometry (TOF 6600, AB SCIEX, Framingham, MA, USA). The analysis conditions and equipment parameters were described in our previous study [ 21 ]. Metabolic-profiling data processing was performed to obtain the retention time and peak area using XCMS software [ 22 ].…”
Section: Methodsmentioning
confidence: 99%